Progression of Obstructive Sleep Apnea Syndrome in Pediatric Patients with Prader-Willi Syndrome - Shi-Bing Wong; Mei-Chen Yang; I-Shiang Tzeng; Wen-Hsin Tsai; Chou-Chin Lan; Li-Ping Tsai (MDPI AG, 2022)
Obstructive sleep apnea syndrome (OSAS) is one of the most common comorbidities in patients with Prader-Willi syndrome (PWS) and causes significant consequences. This observational study was conducted to investigate the progression of OSAS in pediatric patients with PWS, who had not undergone upper airway surgery, through a longitudinal follow-up of their annual polysomnography results. Annual body mass index (BMI), BMI z-score, sleep efficiency and stages, central apnea index (CAI), obstructive apnea-hypopnea index (OAHI), and oxygen saturation nadir values were longitudinally analyzed. At enrollment, of 22 patients (10 boys and 12 girls) aged 11.7 ± 3.9 years, 20 had OSAS. During the 4-year follow-up, only two patients had a spontaneous resolution of OSAS. The average BMI and BMI z-score increased gradually, but CAI and OAHI showed no significant differences. After statistical adjustment for sex, age, genotype, growth hormone use, and BMI z-score, OAHI was associated with the BMI z-score and deletion genotype. In conclusion, OSAS is common in patients with PWS, and rarely resolved spontaneously. Watchful waiting may not be the best OSAS management strategy. Weight maintenance and careful selection of surgical candidates are important for OSAS treatment in patients with PWS.